Dilema Penggunaan Statin dan Aspirin sebagai Alternatif Pencegahan Primer Penyakit Kardiovaskular - Henry Sutanto (Jurnal Kardiologi Indonesia, 2017)
Cardiovascular disease is one of the deadliest diseases in the world. Nowadays, alongside the developments of various medical therapeutic strategies, there is a decreasing trend of cardiovascular mortality. However, this reduction is not adequate and needs to be supported by cardiovascular prevention approaches. Statins and aspirin are two of cardiovascular drugs that are believed to be beneficial in cardiovascular prevention. Their magnificent efficacies in the secondary prevention setting lead them to be used in the primary prevention. However, some safety issues associated with the drugs should be considered. For that reason, based on previous trials and studies, some recommendations regarding the efficacy-safety issues are developed.